VD_FINDINFO HC / 2010 / 74 vom 20. Oktober 2009 - VD Tribunal cantonal (2009)
DROIT DE GARDE, TÉMOIN, DROIT D'ÊTRE ENTENDU, PROCÉDURE | 145 CC, 177 al. 1 CPC, 192 al. 1 CPC, 444 al. 1 ch. 3 CPC, 29 al. 2 Cst.